Health Problems of Older Adults at Tansen Municipality, Palpa, Nepal - Ghimire, Damodar; Prasad, Subhash; Rana, Mohan Singh (Chhahari छहारी, 2026)
Ageing is an inevitable biological process associated with increasing health vulnerabilities. This study assesses the health issues of older adults (aged 60 and above) in Tansen Municipality, Nepal, with a focus on gender disparities, the impact of literacy, and access to social security. A descriptive survey design was employed, with data collected from 147 respondents through a self-administered questionnaire. Findings revealed that 82.5% of females and 62.2% of males reported health problems, indicating the vivid gender disparities in the elders’ health. Approximately dozens of diseases are prevalent among the respondents, where hypertension (46.6%), diabetes (22.3%), gastritis (16.5%), and arthritis (14.56%) ranked in the top four positions, respectively. Illiterate elders faced higher health issues (84.4%). Elders from the Magar community have remarkably high rates of health problems (92.7%), followed by the Brahmin, Newar, and Kshetri, underscoring the need for health education intervention programs to address the socio-cultural practices of elders from an ethnic perspective. About 87% respondents have reported varied suggestions to the government, focusing on the provision of reliable cum accessible social security services regarding the care of the elderly. Results showed that older adults’ health problems were significantly associated with sex, caste, and literacy status. Due to the cross-sectional design, the study lacks the establishment of causal relationships, indicating the need for future longitudinal studies to explore the varied cum deeper findings related to the elders’ health problems. The study highlights the urgent need for gender-sensitive health policies, literacy-based health education, and strengthened elder care programs in Nepal.